Achieving a Developing Village based on the Village Sustainable Development Goals in Tirtonirmolo Village, Bantul Regency - Rahmaddhani, Tiara Wiji; Prasetyoningsih, Nanik (Universitas Muhammadiyah Yogyakarta, 2023)
The Village Minister Regulation No. 21 of 2020 on general guidelines for village development and village community empowerment was enacted to carry out Article 131 paragraph (1) of the Government Regulation concerning Village Law and was issued to achieve the Sustainable Development Goals (SDGs). This research aims to discover and examine village development to achieve The Village SDGs according to village minister regulation No. 21 of 2020 by conducting interviews with related parties in Tirtonirmolo Village using normative and empirical juridical methodologies. This research examined three problem formulations: village minister regulation No. 21 of 2020, the obstacles, and the village government’s efforts. The 2022 village development plan in Tirtonirmolo village to achieve village SDGs followed the stages in village minister regulation No. 21 of 2020. However, there were obstacles to its implementation, particularly at the SDGs data collection stage. The village government has attempted to address this by constantly coordinating with village assistants, engaging IT-savvy human resources to assist with SDGs data collection activities, manually collecting data, and holding the Musrenbangdus.